2018
DOI: 10.1007/s11356-018-2458-4
|View full text |Cite
|
Sign up to set email alerts
|

Duration-dependent effect of exposure to static electric field on learning and memory ability in mice

Abstract: With the rapid development of ultra-high-voltage direct-current (UHVDC) transmission, the strength of environmental static electric field (SEF) around UHVDC transmission lines increased substantially, which has aroused widely public attention on the potential health effects of SEF. In this study, the effect of SEF exposure on learning and memory ability was investigated. Institute of Cancer Research mice were exposed to 56.3 kV/m SEF for a short term (7 days) or long term (49 days). Behaviors in the Morris wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous animal studies have reported that EF affects behavior [27,28] and blood levels of adrenocorticotropic hormone and glucocorticoid [29–35]. The effects of immobilization stress on these stress‐related hormones are reduced in rats and mice by EF exposure for 20 min or more.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have reported that EF affects behavior [27,28] and blood levels of adrenocorticotropic hormone and glucocorticoid [29–35]. The effects of immobilization stress on these stress‐related hormones are reduced in rats and mice by EF exposure for 20 min or more.…”
Section: Discussionmentioning
confidence: 99%